Prognostic and therapeutic significance of microscopic tumor focus in combined hepatocellular-cholangiocarcinoma: a multicenter pathological study - Wang, Han; Xia, Chun-Yan; Sheng, Xia; Zhao, Yun; Chen, Hong-Zhen; Cong, Wen-Ming; He, Miao-Xia; Dong, Hui (Journal of Gastrointestinal Oncology, 2026)
Background: Combined hepatocellular-cholangiocarcinoma (cHCC-CCA) is a rare primary liver cancer lacking personalized pathological parameters. Microscopic tumor foci (MTF), a microscopic intrahepatic metastatic pattern, remain poorly characterized, with unclear prognostic and therapeutic relevance in cHCC-CCA. In this study, the detailed significance of MTF in cHCC-CCA was investigated.Methods: A multicenter study included 310 cHCC-CCA patients who underwent curative-intent hepatectomy. MTF was further graded by its number/distribution (MTF 0: absence of MTF; MTF 1: 1–5 proximal MTFs; MTF 2: >5 proximal MTFs/≥1 distal MTFs) and subclassified by its histology (HCC-type MTF; CCA-type MTF; HCC + CCA-type MTF).Results: MTF was detected in 48.1% (149/310) of patients (MTF 1: 43.2%, MTF 2: 4.8%; HCC-type MTF: 17.7%; CCA-type MTF: 20.6%; HCC + CCA type MTF: 9.7%). MTF positivity correlated with poorer recurrence-free survival (RFS) (median time: 0.23 and 0.89 years), early RFS, and overall survival (OS) (median time: 1.53 and 2.95 years, all P0.1 cm improved RFS, early RFS, and OS, while surgical margin had no effect on MTF-negative patients. Age, tumor diameter, microvascular invasion and perineural invasion independently predicted MTF (area under the curve =0.704); MTF histology was an independent prognostic factor for RFS, early RFS, and OS (all Harrell’s concordance index >0.7).Conclusions: This study standardized the definition of MTF and confirmed its prognostic value in cHCC-CCA. MTF stratification based on its number/distribution and histology enables more precise prognostic assessment. The presence of MTF could guide individualized selection of surgical margin.